Rational design of nitrofuran derivatives: Synthesis and valuation as inhibitors of Trypanosoma cruzi trypanothione reductase - Arias, Diego Gustavo (2017)
The rational design and synthesis of a series of 5-nitro-2-furoic acid analogues are presented. The trypanocidal activity against epimastigote forms of Trypanosoma cruzi and the toxic effects on human HeLa cells were tested. Between all synthetic compounds, three of thirteen had an IC50value in the range of Nfx, but compound 13 exhibited an improved effect with an IC50of 1.0 ± 0.1 μM and a selective index of 70 in its toxicity against HeLa cells. We analyzed the activity of compounds 8, 12 and 13 to interfere in the central redox metabolic pathway in trypanosomatids, which is dependent of reduced trypanothione as the major pivotal thiol. The three compounds behaved as better inhibitors of trypanothione reductase than Nfx (Ki values of 118 μM, 61 μM and 68 μM for 8, 12 and 13, respectively, compared with 245 μM for Nfx), all following an uncompetitive enzyme inhibition pattern. Docking analysis predicted a binding of inhibitors to the enzyme-substrate complex with binding energy calculated in-silico that supports such molecular interaction.